Pengaruh Dukungan Keluarga terhadap Keputusan Karir dengan Efikasi Diri sebagai Variabel Moderator pada Siswa SMA Negeri 4 Samarinda - Aulia Natasyah Putri Hamid; Wahyu Widyatmoko (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to analyze the influence of family support on students' career decisions, with self-efficacy as a moderating variable, in eleventh-grade students at SMA Negeri 4 Samarinda. This study used a quantitative approach with an associative approach. The study population was 384 students, with a sample of 162 students determined through proportional random sampling. Data collection was conducted using a Likert scale instrument covering family support, career decisions, and self-efficacy. Data analysis techniques included descriptive analysis, normality testing, and hypothesis testing using Moderated Regression Analysis (MRA) with the help of SPSS. The results showed that family support significantly influenced students' career decisions (p < 0.05). Self-efficacy was shown to act as a significant moderator by strengthening the relationship between family support and career decisions. These findings indicate that students' career decisions are influenced by both external and internal factors simultaneously, with self-efficacy amplifying the influence of family support on the career decision-making process. These results emphasize the importance of strengthening the role of the family and developing self-efficacy in career guidance services in schools.